From code‐mixing to mode‐mixing in the European context. Issue 2 (June 2016) - JAMES, ALLAN
ABSTRACT: The paper presents four representative case studies of English in Europe influencing local language use in print advertising (Slovenia, Croatia and Italy) and social media online (Wales). For this purpose, three touristic identification displays (including brand name, slogan and logo) and one Instant Messaging conversation between teenagers are investigated, where by close linguistic and graphic analysis of the data it is shown how English serves to express the national identities of product (advertising) and person (e‐communication) projected in the texts. This is achieved by the English mediating the desired identity semiotics by both its verbal and visual properties, which generate the intended social meanings semantically via homophoric reference and intertextuality. In this way, English contacts are co‐realised with the local language as co‐text and/or context in (multilingual and) multimodal discourses where code‐mixing expands to mode‐mixing.